ESTUDIO DE FACTIBILIDAD PARA LA IMPLEMENTACIÒN DE UNA HOSTERÌA EN LA PARROQUIA EL LUCERO, CANTÒN CALVAS, PROVINCIA DE LOJA - CALVA TAMAYO, JENNY MARITZA (2019)
In the province of Loja, canton Calvas, is the parish Lucero, which has a warm and humid climate, this parish has a constant and permanent hydrography that helps the alignment of waterfalls that allows the flora to maintain a natural brightness throughout the year, being attractive for national and international visits. Here arises the need to carry out my thesis project called: "STUDY OF FEASIBILITY FOR THE IMPLEMENTATION OF A HOSTERY IN THE PARISH EL LUCERO, CANTON CALVAS, PROVINCE OF LOJA.", The same that has been raised according to technical conditions , trying to take advantage of the business opportunity in the same place that will be manifested through a thorough investigation, looking for the most appropriate options for the execution of the productive unit. For the development of the project the execution of the following studies was required. The market study with which the demand was analyzed, for this purpose, surveys were made to the plaintiffs and to measure the benefits of the implementation of the inn. The technical study established the location, size and organizational structure of the company, which will be located in the inn; the materials, supplies, equipment and furniture necessary for the project that are in the local market at affordable prices; the organizational structure, constitution and function manuals of the organization that will be called "Hostería Miley", whose task will be to provide lodging services and recreational areas to meet the demand. In the financial study, the initial investment was determined and the profitability of the project was shown as of its first year of work, in addition it would be possible to determine the expenses and therefore the profit in the same period. To carry out this project, a total investment of $ 369,859.69 is required, with its own financing of 76% equivalent to $ 279,859.69; and an external of 24% that amounts to $ 90,000.00, financed by the Father Julián Lorente Cooperative with an interest rate of 12.99% and a term of 5 years. Regarding the financial evaluation, the financial indicators are shown, where the profitability and viability of the project are framed, with a projection of 10 years, the net present value of $ 324,713.97 and an internal rate of return of 31.89% is obtained, giving a cost benefit ratio of 0.02 ctvs. For every dollar invested, the capital recovery period is two years two months. Finally the conclusions, recommendations, bibliography, annexes and index of the project are manifested; On the other hand, the implementation of the Hotel in the Sector is to offer optimal alternatives, according to the current needs and conditions, causing a positive offer to customers, increasing efficiency in terms of the service provided and the requirements of the company, to which that company is owed.